The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1142/s0219633620500133
|View full text |Cite
|
Sign up to set email alerts
|

Towards a theoretical understanding of alkaloid-extract Cytisine derivatives ofRetama monosperma (L.) Boiss. Seeds, as eco-friendly inhibitor for carbon steel corrosion in acidic 1M HCl solution

Abstract: Because of their availability, lower cost, biodegradability, respect for health, environmental standards and their extremely high efficiency [Benmessaoud Left D, Zertoubi M, Irhzo A, Azzi M, Revue: Huiles et extraits de plantes comme inhibiteurs de corrosion pour différents métaux et alliages dans le milieu acide chlorhydrique, J Mater Environ Sci 4:855–866, 2013], the green corrosion inhibitors are currently the most sought after candidates. The ultimate aim of this work is to study the selectivity and reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Using Gaussian 09 software [8], the computational calculations were investigated through the DFT/CAM-B3LYP and DFT/WB97XD functionals to take into account the dispersion correction at long distance. The basis set chosen was aug-cc-pVTZ (correlation consisting polarized basis set) which includes layers of polarization functions -to gain in terms of convergence of the electronic energy towards the complete base limit -and augmented by diffuse functions serving to describe long-range interactions [9], [10]. The results of the conformational analysis of 2.2.3-TMP were slightly different from the DFT/CAM-B3LYP and DFT/WB97XD functionals.…”
Section: Methodsmentioning
confidence: 99%
“…Using Gaussian 09 software [8], the computational calculations were investigated through the DFT/CAM-B3LYP and DFT/WB97XD functionals to take into account the dispersion correction at long distance. The basis set chosen was aug-cc-pVTZ (correlation consisting polarized basis set) which includes layers of polarization functions -to gain in terms of convergence of the electronic energy towards the complete base limit -and augmented by diffuse functions serving to describe long-range interactions [9], [10]. The results of the conformational analysis of 2.2.3-TMP were slightly different from the DFT/CAM-B3LYP and DFT/WB97XD functionals.…”
Section: Methodsmentioning
confidence: 99%
“…Alkaloids were more analogous in these three species of Mediterranean distribution than its profile between the organs of the same species. The major alkaloids detected in stem were retamine and sparteine; while fruits and flowers were dominated by cytisine, lupanine, N-methylcytisine and retamine (El-Shazly et al, 1996); and seeds are the storage organ of cytisine alkaloid (El-Shazly et al, 1996;Sadik et al, 2020). Sadik et al (2020), reported the presence of three alkaloids in R. monosperma seeds in descending percentages as 77.60% cytisine, 13% N-methylcytisine and 9.40% dehydro-cytisine.…”
Section: Phytochemistry Of Retama Speciesmentioning
confidence: 98%
“…The major alkaloids detected in stem were retamine and sparteine; while fruits and flowers were dominated by cytisine, lupanine, N-methylcytisine and retamine (El-Shazly et al, 1996); and seeds are the storage organ of cytisine alkaloid (El-Shazly et al, 1996;Sadik et al, 2020). Sadik et al (2020), reported the presence of three alkaloids in R. monosperma seeds in descending percentages as 77.60% cytisine, 13% N-methylcytisine and 9.40% dehydro-cytisine. While the stem contains ten alkaloids: Ammodendrine, Anagyrine, Cytisine, Dehydrosparteine, 5,6-Dehydrolupanine, 11,12-Dehydrolupanine, Isolupanine, N-methylcytisine, 17-Oxosparteine and Sparteine.…”
Section: Phytochemistry Of Retama Speciesmentioning
confidence: 98%
“…The important parameter descriptors of global reactivity, such as the energy gap (∆E), electronic affinity (EA), ionization potential (EI), electronegativity (χ), chemical hardness (η), global softness (σ), electrophilicity (ω), and electronegativity (χ) index, were calculated using the Equations ( 1)- (7), to explain the chemical reactivity of the newly synthesized molecular [44,45]…”
Section: Dft Computational Studiesmentioning
confidence: 99%